Choosing native tree species for establishing man-made forest: A new perspective for sustainable forest management in changing world - ATOK SUBIAKTO; HENTI HENDALASTUTI RACHMAT; CHIKAYA SAKAI (Biodiversitas Journal of Biological Diversity, 2016)
Subiakto A, Rachmat HH, Sakai C. 2016. Choosing native tree species for establishing man-made forest: A new perspective for sustainable forest management in changing world. Biodiversitas 17: 620-625. Establishment of tree plantation on degraded lands and forest clearly favored some exotic species such as Gmelina arborea, Acacia, and Eucalyptus. High productivity, less harvesting time, and deeper silvicultural knowledge are the beneficial factor for choosing those exotics species. However, the use of a wide variety of native tree species becomes more significantly important in reforestation projects due to the greater biodiversity benefits and widerenvironmental services. This research was carried out as a multiyear observation and continuous experiment to value how native tree species can be prospective alternatives in providing and supporting human need. The performances of two native Indonesian Shorea species, Shorea leprosula and Shorea selanica, were evaluated at a dipterocarp planting trial in two different sites in Indonesia. Growth data was obtained from 15 and 17 years old plots, twelve 100 m X 100 m square plots on mineral soils (Gunung Dahu Experimental Forest/GDEF, Bogor) and eight resembled plots on frequently flooded peat land (PT. Arara Abadi/PT. AA, Riau). Survival rates were varied, ranged from 36-77%, diameter at breast height from 13.7-24.9 cm, tree height from 10.8-16.9 m, mean volume from 0.119m3/tree-0.567 m3/tree, and total volume from 79.420 m3/ha-215.412 m3/ha. Growth rates of planted saplings were affected by species, site and spacing distance. The development of man-made dipterocarps forest in the tropic, especially in South East Asia can be as prospective as developing an exotic fast growing plantation. Eventhough in situ conservation would give the most benefit in conserving genetic resources of native tree species, establishing man-made dipterocarp forest still have higher environmental value than using exotic tree species such as acacia. Moreover, establishing man-made dipterocarp forest is considered more environmental friendly and possess lower to no risk of species invasion compare to those of developing exotic trees plantation.